Pelindungan Hukum Merek Terkenal atas Tindakan Passing Off di Indonesia Berdasarkan Doktrin Likelihood of Confusion - Syifa Rahmatul Ummah Arif (Pusat Riset dan Inovasi Nasional, 2025)
The legal protection of well-known trademarks in Indonesia still faces various challenges, especially in overcoming passing off actions that can harm trademark owners and mislead consumers. The doctrine of likelihood of confusion becomes the main instrument in determining the extent to which the similarity of a brand can cause confusion among consumers. This research aims to analyze the implementation of legal protection of well-known trademarks from the act of passing off in Indonesia, focusing on the Golden Goose case. The research method used is doctrinal legal research with a statute approach and case approach. The data used is secondary data obtained through a literature study of legal regulations, court decisions, and relevant academic literature. The results show that although Indonesia has adopted the doctrine of likelihood of confusion in the Trademark Law, its application still faces various obstacles. The first to file system adopted in trademark registration opens up opportunities for parties with bad intentions to register trademarks that resemble well-known trademarks. This can be seen in the Golden Goose case, where another party registered a similar mark before the legal owner registered in Indonesia, triggering a legal dispute. The court eventually canceled the mark based on significant similarity and potential consumer confusion. This study confirms that it is necessary to strengthen the legal protection mechanism of famous marks, including increased supervision in trademark registration as well as strengthening regulations to prevent passing off.